Efeitos da deriva simulada do glifosato sobre a fotossíntese de genótipos de Coffea canephora - Silva Junior, Genilson Tadeu (2022)
Glyphosate is the main herbicide used to manage weeds in coffee growing. However, glyphosate drift can cause intoxication of coffee trees, with negative effects on photosynthesis, growth and production. However, studies have also shown that underdoses of glyphosate can have hormetic (stimulatory) effects in several crops. Thus, the present study simulated the drift of subdoses of glyphosate in three genotypes of Coffea canephora and investigated the effects on photosynthesis. The experiment was carried out with plants after 4 four years of planting grown under field conditions in Cachoeiro Itapemirim-ES. The three sub-doses of glyphosate (0, 36, 360 g.i.a.ha-¹, which corresponds to 0, 5 and 50% of the recommended dose) were applied directly to the aerial part of the coffee tree. The genotypes treated were: 120 of the 'Robustão Capixaba' variety, 104 of the 'Diamante' variety and 304 of the 'Centenária' variety. Data on gas exchange, chlorophyll a fluorescence and chlorophyll content were evaluated 7 and 15 days after application (DAA) and phytotoxicity symptoms were verified at 7, 15 and 21 DAA. Regardless of the genotype, with 7 DAA, mature leaves that received the herbicide application at a dose of 36 g i.a. ha-¹, when compared with the control, showed a higher (stimulus) net CO2 assimilation rate (23.4%), stomatal conductance (26.9%) and transpiration (29.2%). The photosynthesis stimulus was transitory, not being verified 15 DAA. However, when treated with the highest dose (360 g.i.a.ha-¹), 7 DAA showed decreases in net CO2 assimilation rate (20.3%), stomatal conductance (35.9%) and transpiration (25. 9%). Regardless of the dose, young leaves showed symptoms of phytotoxicity with 7 DAA, symptoms were not evident in mature leaves. It is concluded that the hormetic effect of glyphosate on photosynthesis in C. canephora genotypes should be interpreted with caution as it occurred temporarily. Furthermore, the symptoms of phytotoxicity presented in young leaves of plants treated with the herbicide may limit the photosynthetic capacity after complete expansion of the leaf blade.